Dynamic of Grating Thermal Deformation on Beam Quality for Spectral Beam Combining - Deng, Zhi-feng; Zhan, Sheng-bao; Wang, Ya; Le, Wen-ran; Zha, Shen-long (Frontiers in Physics, 2022)
For spectral beam combining, an experimental system of dynamic beam quality caused by the thermal deformation of a grating has been designed and established. According to the theoretical model established, the distribution of the temperature field, as well as the thermal deformation of the grating, has been analyzed. Further, the combined beam quality and the intensity distribution have been numerically calculated in detail. The results show that the maximum temperature and the grating thermal deformation increase with the extension of irradiation time, resulting in side lobes appearing in the intensity distribution. In the experiment, the measured combined beam quality factor Mx2 was 1.29 without the thermal deformation. When the grating was heated by pump lasers at different times, Mx2 can arrive at 1.34, 1.37, and 1.41, respectively. The results reveal that the combined beam quality increases with the increase in irradiation time and changes rapidly at the beginning of heating, consistent with the theoretical analysis. The discussion and analysis of the dynamic beam quality are potentially valuable for reducing the influence of thermal deformation on the beam quality.